The role of the state in the financing sources’ formation of industrial enterprises’ innovative activities - E. A. Evdokimova; A. Yu. Fomin; M. S. Yumatov (Вестник университета)
Currently, the external conditions for the functioning of industrial enterprises are formed in such a way that the achievement of their goals is seen impossible without the implementation of innovative activities. Due to the high cost of innovations, as well as the need to conduct these processes on an ongoing basis, industrial enterprises lack their own funds to finance innovation activities. The state is interested in the innovative development of industrial enterprises. This is one of the reasons why it participates in the formation of their funding sources. The article substantiates the need for state support, as well as analyzes the options for its provision by type of financing sources. For each type of sources, options for providing large-scale support, implying a large coverage area, as well as point-directed support, are also highlighted.